1995
DOI: 10.1111/j.1476-5381.1995.tb13235.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitric oxide synthase inhibition combined with nitric oxide inhalation in a porcine model of endotoxin shock

Abstract: 1 The present investigation compares the effects of intravenous infusion of the NO synthase inhibitor NG-monomethyl-L-argiine (L-NMMA) with that of an inhalation with NO gas in a porcine model of endotoxin (lipopolysaccharide, LPS) shock. In addition, the effects of the combination of these two treatments were also investigated. 2 Male pigs were anaesthetized and instrumented for the measurement of haemodynamic parameters. Blood samples were withdrawn at different time intervals for determination of blood gase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 31 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…In contrast, in the L‐NNA group there was a selective, significant decrease in pulmonary arterial pressure with no effect on the systemic arterial pressure. While Offner et al have reported similar results, the present study demonstrated the effectiveness of a combined therapy of NO inhalation and NOS inhibitors, even in neonatal animals on day 0 23,25,26 . Furthermore, it was suggested that in cases of endotoxin‐induced hypotension complicated with pulmonary hypertension, NO inhalation carries the risk of aggravating the hypotension.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In contrast, in the L‐NNA group there was a selective, significant decrease in pulmonary arterial pressure with no effect on the systemic arterial pressure. While Offner et al have reported similar results, the present study demonstrated the effectiveness of a combined therapy of NO inhalation and NOS inhibitors, even in neonatal animals on day 0 23,25,26 . Furthermore, it was suggested that in cases of endotoxin‐induced hypotension complicated with pulmonary hypertension, NO inhalation carries the risk of aggravating the hypotension.…”
Section: Discussionsupporting
confidence: 77%
“…Our approach, therefore, is to use a treatment strategy that targets the pulmonary hypertension in addition to the systemic hypotension. Recently, relatively good results have been reported from studies of combined therapy employing NO synthetic inhibitors to treat hypotension and NO inhalation for pulmonary hypertension 23,25,26 . However, most cases of sepsis treated by neonatologists occur within 72 h of birth, when respiratory and circulatory dynamics are adapting to the extra‐uterine environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitric Oxide. Currently there is controversy about whether nitric oxide (NO) suppression with nonselective or selective agents [52], supplementation [53], neither, or both [54] is an adequate measure to deal with NO in trauma and sepsis. There are positive examples of NO synthase blockade in trauma [55,56] and sepsis [57], but there are also studies showing deleterious effects [58,59].…”
Section: Intermediate Mediator Levelmentioning
confidence: 99%